A bolt from the blue : coping with disasters and acute traumas - Saari, Salli, 1944- (Jessica Kingsley Publishers, 2005)
In the wake of 9/11, the world is all too aware of crises but largely underprepared for the psychological repercussions of traumatic events on victims and recovery staff. Salli Saari examines in detail the psychological effect traumatic events can have on an individual, taking the reader step-by-step through each stage of the process of understanding and recovery. She also discusses the role of social support, the media and work in addressing trauma, and what methods can be adopted to help victims cope after a traumatic incident. Based on work within the Finnish organized crisis care network.